Preparation of SrTiO3 nanocubes by CO2 laser vaporization (LAVA) and hydrothermal maturation. Issue 1 (15th November 2021) - Müller, Lenka; Hornig, Philipp; Grabow, Janet; Müller, Frank A.
Abstract : Spherical SrTiO3 nanoparticles were obtained by a laser-induced gas-phase condensation process. Subsequent hydrothermal treatment leads to the formation of faceted, highly crystalline nanocubes with an average size of 35 nm. Abstract : SrTiO3 is of particular interest for numerous applications such as photocatalytic water splitting, as an electrode material for thermoelectrics or as piezoceramics for sensors. Here we report on an advanced CO2 laser vaporization (LAVA) method for the production of faceted, single-phase SrTiO3 nanoparticles with an average particle size of 35 nm. Starting from a coarse SrTiO3 raw powder, spherical SrTiO3 nanoparticles were obtained by a laser-induced gas-phase condensation process. The composition of the nanoparticles corresponds to that of the starting powder, as XRD and FT-IR measurements show. Further hydrothermal treatment at 275 °C for 4 hours leads to the formation of faceted nanocubes with increasing crystallite size, as demonstrated by TEM, HR-TEM and XRD measurements. During a final washing step in 0.1 M HCl, SrCO3 impurities were dissolved and thus single-phase SrTiO3 nanocubes were successfully obtained, as shown by FT-IR, XRD and TEM analyses. The presented process facilitates the production of single-phase, highly crystalline SrTiO3 nanopowders in sufficient quantities for subsequent use in a variety of applications, in particular for hydrogen production by photocatalytic water splitting.